Adaptation of Chinese and English versions of the Psoriatic Arthritis Quality of Life (PsAQoL) scale for use in Singapore. Issue 1 (December 2016) - Leung, Ying; Thumboo, Julian; Rouse, Matthew; McKenna, Stephen
Abstract Background To develop Singapore Chinese and English versions of the Psoriatic Arthritis Quality of Life (PsAQoL) scale that were equivalent to and met the same psychometric and acceptability standards as the original UK measure. Methods Translation of the original PsAQoL into contextualised English and Chinese versions for use in Singapore was performed by professional and lay translation panels. Ten Chinese speaking and ten English speaking local patients were interviewed to assess face and content validity. Psoriatic arthritis (PsA) patients (either Chinese or English speaking) fulfilling the Classification criteria of Psoriatic Arthritis were then invited to participate in a validation survey. Clinical variables, the Health Assessment Questionnaire (HAQ) and the Medical Outcome Short-form 36 (SF-36) were used as comparator instruments for convergent validity. A separate sample of PsA patients were invited to participate in a test-retest postal study, with two weeks between administrations. Results The validation sample included 98 patients (51 % men) with a mean (SD) age of 51.5 (13.8) years. The PsAQoL had excellent internal consistency (Cronbach's α = 0.92) and scores on the measure were moderately correlated with health status measures (pain, HAQ score, SF-36 scores) and patient and physician global assessments. The scale was able to distinguish between groups with active or inactive disease assessed by composite scores, HAQ and minimal disease activity. Test–retest reliability was excellent (r = 0.92). Conclusions This study provides evidence that the adapted English and Chinese versions of the PsAQoL can be used in clinical studies with PsA patients in Singapore.